El genero Panicum (Poaceae: Panicoideae) en el noreste de Mexico - Valdes Reyna, J.=700 1 Zuloaga, F.O.; Morrone, O.; Aragon, L.
(Es, En)
ilus., 17 ref.
Keywords: POACEAE; PANICUM; TAXONOMIA; BIODIVERSIDAD; MEXICO; ZACATE; BOLETIN DE LA SOCIEDAD BOTANICA DE MEXICO